Rancang Bangun Smart Akuarium Ikan Hias Discus Berbasis Internet Of Things - Prasetyo, Bagus Alit; Agung Syukur (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Discus ornamental fish have become a popular hobby among ornamental fish fans. However, to maintain optimal conditions for Discus fish, proper maintenance and careful monitoring are necessary. Therefore, in order to be able to keep discus fish easily, a detection system that utilizes Internet of Things-based technology is needed to ensure fish welfare and water quality. This system uses temperature, pH, Ultrasonic sensors to measure and monitor water conditions. In this research the author developed a smart aquarium for ornamental discus fish based on the Internet of Things with a data transmission mode via a wireless network or (wifi) and integrated with a mobile application platform. With real-time monitoring, it is hoped that we can monitor and maintain aquarium conditions more effectively, reduce the risk of stress in fish, and increase the chances of success in keeping Discus fish. Based on the results of the tests carried out, the system can provide feed and water changes automatically based on the time the user has set in the mobile application. Sensor reading results in the form of temperature, PH and water level values can be monitored easily on the 20x4 LCD and mobile applications in real time.